CONTENT VALIDITY FOR THE RESEARCH INSTRUMENT REGARDING TEACHING METHODS OF THE BASIC PRINCIPLES OF BIOETHICS - Suryadi, Taufik; Alfiya, Fadilah; Yusuf, Muhammad; Indah, Rosaria; Hidayat, Taufik; Kulsum, Kulsum (Universitas Gadjah Mada, 2023)
Background: Bioethics teaching especially related to the basic principles of bioethics can be done by several methods. Currently in the Faculty of Medicine, Universitas Syiah Kuala applying conventional lecture methods, so that other methods are needed to make teaching more interesting. To get the teaching method that students want, a research is carried out through filling out questionnaires. In order for the research questionnaire to be valid, it is necessary to validate the instrument through the content validity of the questionnaire.Methods: The content validity of the questionnaire is carried out by determining the score of each statement item and calculating the Item Content Validity Index (I-CVI), Scale Content Validity Index-Average (S-CVI/Ave), Scale Content Validity Index-Universal agreement (S-CVI/UA), Content Validity Ratio (CVR), Content Validity Index (CVI) and Cohen Kappa Index (CKI) was conducted by 10 assessors from 10 different institutions.Result: The results of the validation of the contents of the questionnaire from the 29 statement items tested obtained that 96% the CVR was ≥ 0.800, 96% I-CVI was ≥ 0.900, CVI was 0.903, S-CVI/UA was 0.551, S-CVI/Ave was 0.952 (recommendation 0.90), average proportion of items judges as relevances across the ten experts 0.949 and CKI was 95,17%.Conclusions: The content validity of this research instrument is very high seen from the CVR, I-CVI, the average value of agreement between assessors (S-CVI/Ave), and the average value of the proportion of statement item relevance (S-CVI/UA) so that it can be developed in various similar studies that discuss the teaching methods of basic principles of bioethics.